Glucose electro-fermentation with mixed cultures: A key role of the Clostridiaceae family. (6th January 2021) - Toledo-Alarcón, Javiera; Fuentes, Laura; Etchebehere, Claudia; Bernet, Nicolas; Trably, Eric
Abstract: Electro-fermentation is a new type of bioprocess combining the concepts of fermentation and electro-microbiology to improve the conversion of organic substrates into valuable fermentation products. During electro-fermentation metabolic profiles could be redirected by the presence of polarized electrodes through changes in the microbial communities in the dark fermentation. This paper aims to investigate the influence of the bacterial community composition on glucose electro-fermentation in batch electro-systems. Our results showed that the initial microbial community significantly impacted the final microbial community and related metabolic patterns. During electro-fermentation, the H2 yield was increased using anaerobic sludge but decreased using activated sludge as inocula. While using other inocula from similar origins, no differences between electro-fermentation and traditional fermentation were evidenced. The relative abundance of Clostridiaceae family members in the inoculum appeared to be a determining factor affecting the global performances. These findings provide new insights on electro-fermentation mecanisms occurring in mixed cultures. Highlights: Inoculum impacted the effect of the Electro-Fermentation process. Clostridiaceae family in mixed cultures had a key role in the Electro-Fermentation mechanisms. Statistical analyses as key tools to determine the microbial influence in Electro-Fermentation.